The “Life” in the Living Law - Harison Citrawan (Advanced Studies on Socio-Economy Development, 2021)
This article explores the concept of ‘living law’ from a spatio-temporal and emotional perspective. Understood as a dynamic and interactive process, living law shapes and reproduces the concepts of law, emotion, and landscape. Based on the semantic findings in decency-related court decisions, this article argues that sensing the living law is to be understood as seeing the physical legal landscape, believing emotional common sense, and anticipating guided by communitarian atmosphere. The daily (legal) experiences captured in case-law are, essentially, assemblages of various meanings and spaces tied up homogeneously in an ideologically manner. Through this examination, living law appears increasingly complex, unstable, and non-linear, especially in terms of its performativity. Law has the potential not only to facilitate social transformation but can negatively impact vulnerable groups. Keywords: Emotion, Landscape, Living Law, Performativity